An observational study comparing the number, the localization and the dermoscopic patterns of melanocytic nevi in cutaneous melanoma and basal cell carcinoma patients - Caner Demircan; Gonca Elcin (Wolters Kluwer Medknow Publications, 2023)
Context: Number of nevi is a risk factor for melanoma and basal cell carcinoma. Studies suggest that the dermoscopic pattern of nevi of melanoma patients may differ from healthy individuals. Similar data in patients with basal cell carcinoma is missing. Aims: The purpose of the study was to determine the number, anatomic distribution and dermoscopic pattern of nevi in melanoma and basal cell carcinoma patients. Settings and Design: An observational prospective study was conducted. Materials and Methods: Total body mole maps of 26 melanoma and 33 basal cell carcinoma patients were analysed. Statistical Analysis Used: Statistical analysis was done using the "IBM SPSS for Windows Version 22.0" package programme. Results: Number of nevi both on head and forearm were found significantly higher in the melanoma group (P = 0.015 and P = 0.031). Most frequent dermoscopic pattern was the complex pattern which was observed in 50.67% of melanoma and in 53.41% of basal cell carcinoma groups. Percentage of nevi with homogenous pattern located on the trunk and percentage of nevi with complex pattern located on the forearm was significantly higher in the melanoma group (P = 0.030 and P = 0.042). Conclusions: Higher number of nevi on the head and forearms; and more nevi showing homogenous pattern on the trunk and complex pattern on the forearms were the hallmarks of nevi in melanoma patients in comparison to basal cell carcinoma patients.